Apoyo en la ejecución de obras civiles en la empresa Consul Construcciones E&E S.A.S Duitama, Boyacá. (2023)
The degree project is carried out through the internship modality which is executed in the private company CONSUL CONSTRUCCIONES E&E SAS of Duitama, Boyacá, among its projects it performs contracting, subcontracting, construction and administrative tasks of civil works; currently it executes constructions mainly in Boyacá, in municipalities such as San Pablo de Borbur, Socotá, Duitama, Paipa, Santa Rosa de Viterbo, Firavitoba in which administrative and technical tasks are performed. The internship covers four projects, the most important of which is the one in San Pablo de Borbur, since it includes support in technical and administrative tasks, while the others are administrative tasks and mainly require filling out forms, minutes and budgets. The work for the rural aqueduct in the Municipality of Socotá requires the execution of administrative activities, mainly with the processing of forms provided by the Corporation Autónoma Regional de Boyacá CORPOBOYACA, in which the required information is taken from the users and the operation stage begins.The construction work of the Vivienda de Interés Social VIS, with 25 Villa Real single-family units in Firavitoba, requires support in the administrative part, with the preparation of the budget corresponding to the houses of 150 m2 of area to be submitted to the municipal mayor's office. The Santa Rosa de Viterbo marketplace project, in which the intern provides support in the verification of quantities, memories and some partial minutes.